2016
DOI: 10.1093/jnen/nlw041
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cell Foam Cell Formation, Apolipoproteins, and ABCA1 in Intracranial Aneurysms: Implications for Lipid Accumulation as a Promoter of Aneurysm Wall Rupture

Abstract: Saccular intracranial aneurysm (sIA) aneurysm causes intracranial hemorrhages that are associated with high mortality. Lipid accumulation and chronic inflammation occur in the sIA wall. A major mechanism for lipid clearance from arteries is adenosine triphosphate-binding cassette A1 (ABCA1)-mediated lipid efflux from foam cells to apolipoprotein A-I (apoA-I). We investigated the association of wall degeneration, inflammation, and lipid-related parameters in tissue samples of 16 unruptured and 20 ruptured sIAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 50 publications
4
48
0
1
Order By: Relevance
“…Oxidized lipids can induce chronic inflammation in atherosclerotic lesion, which is characterized by infiltration of macrophages as in ruptured aneurysm wall. Recent research has also implicated lipid accumulation as a key factor in promoting degeneration of the aneurysm wall via formation of foam cells and subsequent loss of mural cells (10,11). In our study, higher LDL infiltration rate was observed in the ruptured aneurysm wall, implicating lipid accumulation in ruptured aneurysms, which is consistent with the above researches.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Oxidized lipids can induce chronic inflammation in atherosclerotic lesion, which is characterized by infiltration of macrophages as in ruptured aneurysm wall. Recent research has also implicated lipid accumulation as a key factor in promoting degeneration of the aneurysm wall via formation of foam cells and subsequent loss of mural cells (10,11). In our study, higher LDL infiltration rate was observed in the ruptured aneurysm wall, implicating lipid accumulation in ruptured aneurysms, which is consistent with the above researches.…”
Section: Discussionsupporting
confidence: 92%
“…For example, patients having a high lipid level or high blood pressure does not necessarily indicate a high lipid accumulation in the aneurysm wall and vice versa. LDL, though widely recognized as risk factors for cardiovascular and cerebrovascular disease, was not found to be associated with cerebral aneurysm rupture in a recent clinical study (12), which seems to conflict with findings from a histopathology study (9,10). However, it is important to note that despite LDL not recognized as a risk factor, the use of a lipidlowering agent was found to be able to reduce the risk of rupture (12).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…52 Clinically, one of the most pertinent questions regarding the biology of aneurysm formation is how to stabilize small inceptions of aneurysms or small aneurysms and prevent them from growing to a size in which rupture becomes increasingly likely. 22,31,72 The presence of MCP1 expression and macrophages 9,27,34,55 in human IA walls implies that the same molecular mechanisms as in IA initiation might be involved in IA progression, at least in the formation of daughter aneurysms or so-called "secondary pouches" that tend to form in the IA sacs at regions with high WSS. 15 In addition to high-WSS areas, MCP1 can be also induced in IA regions with low WSS.…”
Section: Flow-triggered Inflammation-mediated Remodeling In Aneurysm mentioning
confidence: 99%
“…It is a major health care concern since the rupture of an aneurysm can lead to subarachnoid hemorrhage, placing the patient in great danger [2,3]. It has been suggested that the occurrence, development, and even rupture of aneurysms are mainly caused by hemodynamic factors [4].…”
Section: Introductionmentioning
confidence: 99%